MAYBE Initial complexity problem: 1: T: (?, 1) f0(a, b, c) -> f2(a, d, c) [ 0 >= a ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] (1, 1) f1(a, b, c) -> f0(a, b, c) start location: f1 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] (1, 1) f1(a, b, c) -> f0(a, b, c) start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a, b, c) with all transitions in problem 2, the following new transition is obtained: f1(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] We thus obtain the following problem: 3: T: (1, 2) f1(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] with all transitions in problem 3, the following new transition is obtained: f1(a, b, c) -> f0(a + 2*c - 1, b, c - 2) [ a >= 1 /\ a + c >= 1 ] We thus obtain the following problem: 4: T: (1, 3) f1(a, b, c) -> f0(a + 2*c - 1, b, c - 2) [ a >= 1 /\ a + c >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 2*c - 1, b, c - 2) [ a >= 1 /\ a + c >= 1 ] with all transitions in problem 4, the following new transition is obtained: f1(a, b, c) -> f0(a + 3*c - 3, b, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] We thus obtain the following problem: 5: T: (1, 4) f1(a, b, c) -> f0(a + 3*c - 3, b, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 3*c - 3, b, c - 3) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 ] with all transitions in problem 5, the following new transition is obtained: f1(a, b, c) -> f0(a + 4*c - 6, b, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] We thus obtain the following problem: 6: T: (1, 5) f1(a, b, c) -> f0(a + 4*c - 6, b, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 4*c - 6, b, c - 4) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 ] with all transitions in problem 6, the following new transition is obtained: f1(a, b, c) -> f0(a + 5*c - 10, b, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] We thus obtain the following problem: 7: T: (1, 6) f1(a, b, c) -> f0(a + 5*c - 10, b, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 5*c - 10, b, c - 5) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 ] with all transitions in problem 7, the following new transition is obtained: f1(a, b, c) -> f0(a + 6*c - 15, b, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] We thus obtain the following problem: 8: T: (1, 7) f1(a, b, c) -> f0(a + 6*c - 15, b, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 6*c - 15, b, c - 6) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 ] with all transitions in problem 8, the following new transition is obtained: f1(a, b, c) -> f0(a + 7*c - 21, b, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] We thus obtain the following problem: 9: T: (1, 8) f1(a, b, c) -> f0(a + 7*c - 21, b, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 7*c - 21, b, c - 7) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 ] with all transitions in problem 9, the following new transition is obtained: f1(a, b, c) -> f0(a + 8*c - 28, b, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] We thus obtain the following problem: 10: T: (1, 9) f1(a, b, c) -> f0(a + 8*c - 28, b, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 8*c - 28, b, c - 8) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 ] with all transitions in problem 10, the following new transition is obtained: f1(a, b, c) -> f0(a + 9*c - 36, b, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] We thus obtain the following problem: 11: T: (1, 10) f1(a, b, c) -> f0(a + 9*c - 36, b, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 9*c - 36, b, c - 9) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 ] with all transitions in problem 11, the following new transition is obtained: f1(a, b, c) -> f0(a + 10*c - 45, b, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] We thus obtain the following problem: 12: T: (1, 11) f1(a, b, c) -> f0(a + 10*c - 45, b, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 10*c - 45, b, c - 10) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 ] with all transitions in problem 12, the following new transition is obtained: f1(a, b, c) -> f0(a + 11*c - 55, b, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] We thus obtain the following problem: 13: T: (1, 12) f1(a, b, c) -> f0(a + 11*c - 55, b, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 11*c - 55, b, c - 11) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 ] with all transitions in problem 13, the following new transition is obtained: f1(a, b, c) -> f0(a + 12*c - 66, b, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] We thus obtain the following problem: 14: T: (1, 13) f1(a, b, c) -> f0(a + 12*c - 66, b, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 12*c - 66, b, c - 12) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 ] with all transitions in problem 14, the following new transition is obtained: f1(a, b, c) -> f0(a + 13*c - 78, b, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] We thus obtain the following problem: 15: T: (1, 14) f1(a, b, c) -> f0(a + 13*c - 78, b, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 13*c - 78, b, c - 13) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 ] with all transitions in problem 15, the following new transition is obtained: f1(a, b, c) -> f0(a + 14*c - 91, b, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] We thus obtain the following problem: 16: T: (1, 15) f1(a, b, c) -> f0(a + 14*c - 91, b, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f0(a + 14*c - 91, b, c - 14) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 ] with all transitions in problem 16, the following new transition is obtained: f1(a, b, c) -> f0(a + 15*c - 105, b, c - 15) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 /\ a + 14*c - 91 >= 1 ] We thus obtain the following problem: 17: T: (1, 16) f1(a, b, c) -> f0(a + 15*c - 105, b, c - 15) [ a >= 1 /\ a + c >= 1 /\ a + 2*c - 1 >= 1 /\ a + 3*c - 3 >= 1 /\ a + 4*c - 6 >= 1 /\ a + 5*c - 10 >= 1 /\ a + 6*c - 15 >= 1 /\ a + 7*c - 21 >= 1 /\ a + 8*c - 28 >= 1 /\ a + 9*c - 36 >= 1 /\ a + 10*c - 45 >= 1 /\ a + 11*c - 55 >= 1 /\ a + 12*c - 66 >= 1 /\ a + 13*c - 78 >= 1 /\ a + 14*c - 91 >= 1 ] (?, 1) f0(a, b, c) -> f0(a + c, b, c - 1) [ a >= 1 ] start location: f1 leaf cost: 1 Complexity upper bound ? Time: 2.763 sec (SMT: 2.641 sec)